Microarray analysis of gene expression in olive flounder liver infected with viral haemorrhagic septicaemia virus (VHSV). (February 2016) - Cho, Hyun Kook; Kim, Julan; Moon, Ji Young; Nam, Bo-Hye; Kim, Young-Ok; Kim, Woo-Jin; Park, Jung Youn; An, Cheul Min; Cheong, Jaehun; Kong, Hee Jeong
Abstract: The most fatal viral pathogen in olive flounder Paralichthys olivaceus, is viral hemorrhagic septicemia virus, which afflicts over 48 species of freshwater and marine fish. Here, we performed gene expression profiling on transcripts isolated from VHSV-infected olive flounder livers using a 13 K cDNA microarray chip. A total of 1832 and 1647 genes were upregulated and down-regulated over two-fold, respectively, after infection. A variety of immune-related genes showing significant changes in gene expression were identified in upregulated genes through gene ontology annotation. These genes were grouped into categories such as antibacterial peptide, antigen-recognition and adhesion molecules, apoptosis, cytokine-related pathway, immune system, stress response, and transcription factor and regulatory factors. To verify the cDNA microarray data, we performed quantitative real-time PCR, and the results were similar to the microarray data. In conclusion, these results may be useful for the identification of specific genes or for the diagnosis of VHSV infection in flounder. Highlights: We performed expression profiling in VHSV-infected flounder livers using a 13 K cDNA chip. A total of 3479 genes were regulated over two-fold after infection. GO analysis revealed the up-regulation of immune-related genes after infection. These results may be useful for the identification of VHSV infection-responsible gene in flounder.